PENGARUH MUTU PELAYANAN PERPUSTAKAAN TERHADAP KECEPATAN MEMPEROLEH INFORMASI BAHAN PUSTAKA BAGI MAHASISWA PRODI MPI ANGKATAN 2018 DI IAIN MADURA - Wijaya, Tukad Adi; Thoha, Mohammad (re-JIEM (Research Journal of Islamic Education Management), 2020)
Service is an activity whose implementation is carried out by holding relationships, both directly and indirectly. The service referred to here is how the service process is implemented and carried out in the library of IAIN Madura to facilitate information retrieval of library materials for students, especially MPI study program students in class 2018. This is evident from the results of statistical analysis showing that the work r 0.622 is consulted with product criticism moment at the value of N = 32 with the value "r" of work is greater than the "r" table of product moment both at 95% intervals and at 99% intervals where it shows a value of 0.349. Thus it can be said that there is a positive correlation between the two research variables. how big is the relationship between the quality of library services to the speed of obtaining library material information for MPI study program batch 2018 in Madura IAIN r work is consulted with a product moment correlation interpretation table, where r work is in the range of values between 0.600 to 0.800 which means the second correlation or urgency the variable is at a sufficient level of significance.